2003
DOI: 10.1177/1073191103255493
|View full text |Cite
|
Sign up to set email alerts
|

Three Factors of the Comprehensive System for the Rorschach and their Relationship to Wechsler IQ Scores in an Adolescent Sample

Abstract: Principal axis factor analyses of the Rorschach Comprehensive System (CS) in a clinical sample of 152 adolescents yielded three clearly defined factors: Synthesized Complexity (defined by Zf, DQ+, and F%), Productivity (defined by R, D, and Dd), and Form Quality (defined by X+%, F+%, and X-%). Variables on the Synthesized Complexity and Form Quality factors were generally correlated with Wechsler Full Scale IQ, Verbal IQ, and Performance IQ scores. Overall, the factors in this adolescent sample replicated fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…In line with most of the theories just described, a wide body of empirical research has shown that M responses are associated consistently with ideational and social processes including field independence (Witkin, Dyk, Faterson, Goodenough, & Karp, 1962), effective interpersonal relations and behaviors (Exner, 2003), ego strength and introversion (Greenwald, 1991;Hix et al, 1994), ability to cognitively process emotions (Porcelli & Meyer, 2002;Porcelli & Mihura, 2010;Ruhe & Lynn, 1987), creativity (Ferracuti, Cannoni, Burla, & Lazzari, 1999), dream recall (Orlinsky, 1966), and intelligence (Gallucci, 1989;Wood, Krishnamurthy, & Archer, 2003). M has also been associated with sensory deprivation (Bendick & Klopfer, 1964), electromyography-based muscle potentials (Steele & Kahn, 1969), ability to discriminate florid and withdrawn schizophrenics from healthy subjects (Di Nuovo, Laicardi, & Tobino, 1988), and symptom improvement after psychotherapy (Exner & Andronikof-Sanglade, 1992;Weiner & Exner, 1991).…”
Section: Human Movement In the Rorschach Testmentioning
confidence: 69%
“…In line with most of the theories just described, a wide body of empirical research has shown that M responses are associated consistently with ideational and social processes including field independence (Witkin, Dyk, Faterson, Goodenough, & Karp, 1962), effective interpersonal relations and behaviors (Exner, 2003), ego strength and introversion (Greenwald, 1991;Hix et al, 1994), ability to cognitively process emotions (Porcelli & Meyer, 2002;Porcelli & Mihura, 2010;Ruhe & Lynn, 1987), creativity (Ferracuti, Cannoni, Burla, & Lazzari, 1999), dream recall (Orlinsky, 1966), and intelligence (Gallucci, 1989;Wood, Krishnamurthy, & Archer, 2003). M has also been associated with sensory deprivation (Bendick & Klopfer, 1964), electromyography-based muscle potentials (Steele & Kahn, 1969), ability to discriminate florid and withdrawn schizophrenics from healthy subjects (Di Nuovo, Laicardi, & Tobino, 1988), and symptom improvement after psychotherapy (Exner & Andronikof-Sanglade, 1992;Weiner & Exner, 1991).…”
Section: Human Movement In the Rorschach Testmentioning
confidence: 69%
“…The literature on cognitive capacity provides an empirical foundation for our hypotheses, given that depletion impairs cognitive processing ability (Hagger et al, 2010). For instance, Wood, Krishnamurthy, and Archer (2003) factored 19 Comprehensive System variables, finding three factors of Productivity, Synthesized Complexity, and Form Quality; the latter two were positively correlated with IQ scales. Acklin and Fechner-Bates (1989) found Whole responses with synthetic organization were positively correlated with five Wechsler Adult Intelligence Scale–Revised IQ scales (not Verbal Comprehension), whereas responses using common locations and lacking synthetic organization were inversely correlated with Verbal IQ, Performance IQ, and Full Scale IQ.…”
mentioning
confidence: 99%
“…Reliability and validity estimates of the Rorschach are described extensively elsewhere (Exner, 1993(Exner, , 2003Exner & Weiner, 1995;Viglione, 1999;Viglione & Hilsenroth, 2001;Wagner, Alexander, Roos, & Adair, 1986;Weiner, 1996Weiner, , 1997. For example, research studies with children suggest that various conceptually related Rorschach scores reflect developmentally appropriate trends in emotional modulation and perceptual accuracy (Weiner, 1996), relate to measures of global cognitive functioning (Wood, Krishnamurthy, & Archer, 2003), learning disability status (Acklin, 1990;Acklin & Fechner-Bates, 1989;Cruz, Brier, & Reznikoff, PERCEPTUAL-ORGANIZATIONAL CHARACTERISTICS 791 1997), and are reflective of thought disorder (Smith, Baity, Knowles, & Hilsenroth, 2001;Stokes, Pogge, Grosso, & Zaccario, 2001), conduct disorder (Liebman, Porcerelli, & Abell, 2005;Smith, Gacono, & Kaufman, 1997); PTSD (Holaday, 2000), and ADHD (Bartell & Solanto, 1995). Because of their purported relationship to aspects of visual processing, organization, and representation and perceptual accuracy (Exner, 1993(Exner, , 2000, the following Rorschach variables were examined: DQ, FQ, Zd, location (W, D, Dd, S), WDA%, and PTI.…”
Section: Methodsmentioning
confidence: 98%
“…Prior studies have shown a relationship between global intelligence and Rorschach indices of developmental quality, form quality, and response production (e.g., Wood et al, 2003). Given the positive correlations between ROCF Copy and ROCF Delay and FSIQ in our data, we also controlled for the effects of FSIQ for all variables.…”
Section: Perceptual-organizational Characteristicsmentioning
confidence: 94%